Deskripsi Kemampuan Pemecahan Masalah Matematika Siswa dalam Pokok Pembahasan Distribusi Binomial - Fatwa, Indah Ainun; Mulbar, Usman; Bernard (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2018)
This research is a descriptive research with qualitative approach aimed to describe problem solving abilities of mathematics students class XII MIA. By taking 6 students as subject. Instruments in this study are the researchers themselves as the main instrument and as a supporting instrument, namely the problem-solving skills test, interview guidelines. The results showed: (1) students with high ability level can determine the informations contained in the problem complete and precise, plan the problem-solving very well, implement the plan of problem-solving and can explain the problem-solving steps used with the correct results, and check back problem-solving steps used thoroughly and the answers. (2) students with medium ability to determine the information contained in the problem with complete but not appropriate, have a good problem-solving plan, explain the problem-solving steps used with less correct results, and don't re-examine the problem-solving steps used thoroughly and the answer. (3) students with low ability level can determine the information contained in the problem with complete and less precise, have a problem-solving plan that can help him in resolving the problem correctly, solve the problem with incorrect results, and don't re-examine the troubleshooting steps used thoroughly with the answers.